E-commerce technology adoption framework by New Zealand small to medium size enterprises - Rashid, M.A. (Massey University, 2001)
This paper attempts to highlight a framework for the adoption of electronic commerce (EC) technologies in New Zealand with specific interest in the small to medium-size enterprise (SME) sector of the economy. The main thrust of the research was to develop the framework for EC adoption by the New Zealand SMEs and hence study the accelerators and impediments to the adoption and diffusion of EC technologies. The paper shows how IS/IT adoption and diffusion theories and practicalities can be explored for developing the proposed EC adoption framework. It is argued that results from research case studies based on the framework are able to identify the factors influencing and leading to the adoption of e-commerce technologies by the New Zealand SMEs.
Keywords: Electronic commerce; E-commerce; SMEs; Small business